The role of immunotherapy in the treatment of lip squamous cell carcinoma: A series of six cases and a review of the current literature - Ido Amir; Nir Tsur; Itamar Averbuch; Gideon Bachar; Noga Kurman (Oral Oncology Reports)
Background: Squamous cell carcinoma (SCC) of the lip is a distinct subtype of oral cavity SCC, accounting for about 10–20 % of all oral cavity cancers. According to National Comprehensive Cancer Network (NCCN) guidelines, treatment consists of surgical resection with adjuvant radiotherapy or chemoradiotherapy as indicated. The role of immunotherapy as a treatment modality remains unclear. Methods: We identified six patients with SCC of the lip who had locally advanced or recurrent disease and treated with PD-1 inhibitors, either as monotherapy or as part of a chemo-immuno regimen. Three patients were diagnosed with locoregional recurrences after conventional treatment failure, one of whom concurrently diagnosed with distant metastases. Two cases involved treatment with immunotherapy as an alternative to surgery or radiotherapy. Clinical and radiological responses were assessed, and side effects were recorded. Results: All patients exhibited complete clinical response, five showed complete radiological responses per PET-CT. One patient was yet to be assessed radiologically. Another had a PET-avid supraclavicular node negative for malignancy. The median follow-up time since treatment initiation was 11.49 months (IQR 7.77 - 29.03). Adverse effects included severe myositis (n = 1), arthralgia (n = 1), psoriasis (n = 1), esophagitis (n = 1), mild hepatitis (n = 1) and pruritus (n = 2). Management included corticosteroids (topical or systemic) and/or 2nd generation antihistamines and treatment cessation as indicated. Conclusion: Immunotherapy shows promise for lip SCC after conventional treatment failure or as an alternative to surgery or radiotherapy in unsuitable candidates, suggesting a tumor biology resembling cutaneous rather than oral cavity SCC. Patients should be closely monitored for potential side effects.